ON THE FEATURES OF THE DEVELOPMENT OF FESTIVAL TOURISM (ACCORDING TO THE MATERIALS OF THE LVIV OBLAST) - LUSHCHYK, MARIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
We watched, every year, tourist events, which play an important role in shaping tourist flows and have a positive impact on the development of tourist infrastructure, are causing increasing resonance and interest of potential tourists. Therefore, it is worth paying attention to festival resources, the potential of which is unlimited, but is the most attractive for use in cognitive, youth, ethnic and adventure tourism.The theoretical foundations of festival tourism, as well as its regional aspects of development are described in the scientific literature very little. The object of study of this article is the features of the development of festival tourism in the region, and the subject of scientific research is the features of the organization of festival tourism in conditions of increased epidemic risks. The purpose of the study is to substantiate the scientific principles and develop practical recommendations for the development of festival tourism in the region in conditions of increased epidemic risks.The paper describes the approaches to the interpretation of the concept of "festival tourism" in the scientific literature, presents the main features that determine the content of festival tourism and describes the mandatory components of any festival, establishes the place of festival tourism in the system of mass tourism. a number of features (according to the direction of tourist flows, the scale of territorial coverage, the duration of the trip, the demographic and social composition of travel participants, the nature of the organization, the intensity, the mode of movement). The current state of development of festival tourism in the region is analysed. The calendar of festivals of Lviv region is made and the characteristic of the most known festivals of the city and area is given, the special attention is paid to the description of events of tourist character. New organizational and managerial decisions at the organization of festivals of the Lviv region in quarantine conditions are described.
Keywords: tourism; event tourism; festival tourism; festivals